Case Report: Treatment and management of a child at high risk of caries - Fan, Wen; Chen, Qianjing; Zhang, Yushan; Feng, Jixian; Zhai, Yuankun; He, Baojie (Frontiers in Pediatrics, 2023)
Introduction: Caries are at the forefront of childhood diseases. Although childhood caries usually is not life-threatening, it can affect children’s dental-maxillofacial development and mental health and place significant financial and psychological burdens on parents. As the focus of childhood dental caries shifts to early diagnosis and prevention rather than restorative dentistry alone, screening children at a high risk of dental caries is urgent. Appropriate caries-prevention measures and treatment sequences can effectively reduce the occurrence and development of dental caries in children. Case: We report the case of a 7-year-old boy presenting with a high risk of dental caries involving multiple primary teeth and premature eruption of the permanent teeth. We shifted the child’s caries status from high to moderate likelihood. At the 9-month post-treatment follow-up, the patient had no new dental caries, and the length and width of the dental arch were effectively maintained. Conclusion: Oral health education, dental plaque removal in a regular basis, and fluoride application contribute to caries management.